A note on abelian groups supporting unital rings - Woronowicz, Mateusz (Annales Mathematicae Silesianae, 2024)
Non-nil abelian groups are classified on which every ring, different from the zero-ring, is unital. It is shown that the assumption on the associativity of the considered rings does not influence the obtained classification. A significant mistake made by other authors studied this topic is corrected.